1980
DOI: 10.1289/ehp.8035131
|View full text |Cite
|
Sign up to set email alerts
|

Mucus glycoprotein secretion by tracheal explants: effects of pollutants.

Abstract: Tracheal slices incubated with radioactive precursors in tissue culture medium secrete labeled mucus glycoproteins into the culture medium. We have used an in vivtro approach, a combined method utilizing exposure to pneumotoxins in vivo coupled with quantitation of mucus secretion rates in vitro, to study the effects of inhaled pollutants on mucus biosynthesis by rat airways. In addition, we have purified the mucus glycoproteins secreted by rat tracheal explants in order to determine putative structural change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The small amount of labeling of Fraction I1 with 3sS is also consistent with our data from human tracheal explants [ 4 ] and rat tracheal explants [5]. It is not clear whether the even smaller amount of "S in Fraction I (less than 1 % of the total) is incorporated into glycoprotein or is a contaminating impurity; this problem is discussed elsewhere [4].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The small amount of labeling of Fraction I1 with 3sS is also consistent with our data from human tracheal explants [ 4 ] and rat tracheal explants [5]. It is not clear whether the even smaller amount of "S in Fraction I (less than 1 % of the total) is incorporated into glycoprotein or is a contaminating impurity; this problem is discussed elsewhere [4].…”
Section: Resultssupporting
confidence: 80%
“…2(b)] is observed from the tracheal explant medium that is absent from the HTE-B cell culture medium. This additional fraction that is apparently absent from the HTE-B cell culture medium contains glycopeptides with terminal sialic acid residues, based on their susceptibility to neuraminidase digestion and their binding properties to specific lectins [ 5 ] . The concentration of LiCl at which the various The additional sialic-acid-containing peak from the tracheal medium is eluted at about 0.25 M LiC1, so is clearly separable from those fractions designated Peaks I1 and 111 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies suggest that IL-1␤ or TNF-␣ (1), or even reactive oxygen species (26), may play a role in this process. A number of soluble by-products arising from epithelial lining fluid, and cellular reactions with O 3 , may also upregulate transcription factors and proinflammatory genes (27,28). Our data suggest that the susceptibility to acute O 3 exposure is a complex trait with strain variation in expression, combination, and distribution of several main phenotypic features (e.g., lung inflammation, increased lavageable protein levels, and airway epithelial cell injury/proliferation).…”
Section: Discussionmentioning
confidence: 77%
“…The methodology used in the present study is identical to that currently used for animal studies in our laboratory (13,14). We have studied radionuclide-labeled mucus glycoproteins from rat and monkey tracheal explants extensively (10,II,16), and have found that papain digestion of tissue culture medium, although avoiding contamination by oropharyngeal secretions or products of airway inflammation, yields a sufficient amount of purified mucus glycopeptides to permit their relatively sharp resolution on chromatography. The primary purpose of the present study was to examine possible differences between the respiratory mucus glycoproteins of CF and non-CF subjects.…”
Section: Speculationmentioning
confidence: 97%